A micromechanics approach for the effective thermal conductivity of composite materials with general linear imperfect interfaces. (15th September 2018) - Koutsawa, Yao; Karatrantos, Argyrios; Yu, Wenbin; Ruch, David
Abstract: The mechanics of structure genome has been extended to heat conduction problem of composite materials with a general linear thermal imperfect interface model. This full field micromechanics approach is applied to predict the effective thermal conductivity of composite materials containing thermal imperfect contact between the matrix and the reinforcements. Examples of spheroidal particles reinforced composites are used to demonstrate the robustness and accuracy of this micromechanics theory. The size-dependency of the overall thermal conductivity shows the importance of imperfect interfaces in modeling the thermal behavior of composite materials. The proposed micromechanics method is versatile and can be applied for estimating the effective thermal conductivity of nanocomposite materials.